Therapy for Stage IV Non–Small-Cell Lung Cancer With Driver Alterations: ASCO and OH (CCO) Joint Guideline Update. Issue 9 (20th March 2021) - Hanna, Nasser H.; Robinson, Andrew G.; Temin, Sarah; Baker, Sherman; Brahmer, Julie R.; Ellis, Peter M.; Gaspar, Laurie E.; Haddad, Rami Y.; Hesketh, Paul J.; Jain, Dharamvir; Jaiyesimi, Ishmael; Johnson, David H.; et al.
Abstract : PURPOSE: To provide evidence-based recommendations updating the 2017 ASCO guideline on systemic therapy for patients with stage IV non–small-cell lung cancer (NSCLC) with driver alterations. A guideline update for systemic therapy for patients with stage IV NSCLC without driver alterations was published separately. METHODS: The American Society of Clinical Oncology and Ontario Health (Cancer Care Ontario) NSCLC Expert Panel updated recommendations based on a systematic review of randomized controlled trials (RCTs) from December 2015 to January 2020 and meeting abstracts from ASCO 2020. RESULTS: This guideline update reflects changes in evidence since the previous update. Twenty-seven RCTs, 26 observational studies, and one meta-analysis provide the evidence base (total 54). Outcomes of interest included efficacy and safety. Additional literature suggested by the Expert Panel is discussed. RECOMMENDATIONS: All patients with nonsquamous NSCLC should have the results of testing for potentially targetable mutations (alterations) before implementing therapy for advanced lung cancer, regardless of smoking status recommendations, when possible, following other existing high-quality testing guidelines. Most patients should receive targeted therapy for these alterations: Targeted therapies against ROS -1 fusions, BRAF V600e mutations, RET fusions, MET exon 14 skipping mutations, and NTRK fusions should be offered to patients, either as initial or second-line therapy when not given in the first-line setting. New or revised recommendations include the following: Osimertinib is the optimal first-line treatment for patients with activating epidermal growth factor receptor mutations (exon 19 deletion, exon 21 L858R, and exon 20 T790M); alectinib or brigatinib is the optimal first-line treatment for patients with anaplastic lymphoma kinase fusions. For the first time, to our knowledge, the guideline includes recommendations regarding RET, MET, and NTRK alterations. Chemotherapy is still an option at most stages. Additional information is available at www.asco.org/thoracic-cancer-guidelines .